Air gap MMF based prediction of eddy current loss in the PMs of concentrated winding brushless machines. Issue 5 (19th August 2014) - Masmoudi, Asma; Masmoudi, Ahmed; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper aims at an analytical approach-based prediction of the eddy current loss in the PMs of a concentrated winding machine equipped with 12 slots in the stator and 10 poles in the rotor. Design/methodology/approach The investigation of the PM eddy current loss has been carried out using an analytical model and a 2D time-stepped transient finite element analysis (FEA). Findings It has been found, in the case of the treated machine, that just the subharmonic of rank one and the harmonic of rank seven have significant contributions to the eddy current loss in the PMs. Research limitations/implications A shift between the results yielded by the developed analytical model and those computed by FEA has been noticed. This limitation is mainly due to the slotting effect which has been omitted in the analytical model. Practical implications Fractional slot PM machines are currently given an increasing attention in automotive applications. The prediction of their iron loss in an attempt to rethink their design represents a crucial efficiency benefit. Originality/value The analytical prediction of the eddy current loss in each PM then in all PMs and their validation by FEA represent the major contribution of this work.